Efektivitas Layanan Bimbingan Kelompok Teknik Role Playing untuk Mengatasi Culture Shock pada Mahasiswa Rantau Suku Mandailing - Tuzahra, Sunia; Harahap, Ade Chita Putri; Manurung, Purbatua (IAI Nasional Laa Roiba Bogor, 2024)
Culture shock is a condition where individuals experience anxiety when they are in a new environment, especially individuals who have migrated. There are students at the State Islamic University of North Sumatra majoring in Islamic Education Counseling Guidance (BKPI) Stambuk 2023 who have high levels of culture shock, so efforts are needed to reduce Culture shock for students through role playing technique group guidance services. The aim of this research is to determine the effectiveness of group guidance services using role playing techniques. This research uses a quantitative approach with a pre-experimental research type, the method used in the research uses the One Group Pretest Posttest Design method, using a research sample of 8 students obtained using a purposive sampling technique. Research data was collected using the Culture shock scale. After obtaining the data, it was analyzed using the Wilxocon test with the help of SPSS version 22, Asymp probability data was obtained. Sig (2-tailed) 0.012 < 0.05 means that there is a significant value in the value before and after treatment, which means that the role playing technique group guidance service is effective in overcoming culture shock in overseas Mandailing ethnic students.